2014
DOI: 10.1016/j.redox.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Defective mitophagy driven by dysregulation of rheb and KIF5B contributes to mitochondrial reactive oxygen species (ROS)-induced nod-like receptor 3 (NLRP3) dependent proinflammatory response and aggravates lipotoxicity

Abstract: High-fat diet (HFD) and inflammation are the key contributors to insulin resistance and type 2 diabetes (T2D). Previous study shows fatty acid-induced accumulation of damaged, reactive oxygen species (ROS)-generating mitochondria, and this in turn activates the NLRP3 inflammasome interference with insulin signaling. Our previous research shows NLRP3 inflammasome activation signal originates from defects in autophagy. Yet how the fatty acid related to mitophagy alteration leads to the activation of NLRP3-ASC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 49 publications
5
44
0
1
Order By: Relevance
“…A similar result was observed in INS(rat insulinoma cell)-823/13 cells under diabetic conditions treated with 0.5mM PA(palmitic acid) + 20mM Glucose ( Figure 1C). Previous studies showed that treatment with high glucose and palmitate induced Miro1 degradation via a Ca2+-dependent pathway (7). Similar to these results, a decline in Miro1 staining was observed in STZ mice (Supplementary S3) ( Figure 1B).…”
Section: Miro1 Is Decreased In Pancreatic Beta Cells and Islets Undersupporting
confidence: 86%
See 1 more Smart Citation
“…A similar result was observed in INS(rat insulinoma cell)-823/13 cells under diabetic conditions treated with 0.5mM PA(palmitic acid) + 20mM Glucose ( Figure 1C). Previous studies showed that treatment with high glucose and palmitate induced Miro1 degradation via a Ca2+-dependent pathway (7). Similar to these results, a decline in Miro1 staining was observed in STZ mice (Supplementary S3) ( Figure 1B).…”
Section: Miro1 Is Decreased In Pancreatic Beta Cells and Islets Undersupporting
confidence: 86%
“…Mitochondrial activity is necessary for the process of cell proliferation and metabolism, and mitochondrial dysfunction is associated with a variety of human diseases, including cancer [5], diabetes [3] and age-related diseases [6]. Increasing evidence suggests that mitophagy maintains mitochondrial integrity and quality control not only by selectively removing dysfunctional or damaged mitochondria [7][8][9], but also by promoting biosynthesis of new mitochondria [10]. Recently, it has been found that before the onset of mitophagy, Cells block mitochondrial motility by causing mitochondrial Rho GTPase (Miro) degradation and ubiquitination of mitochondrial proteins to promote their identification and recruitment to autophagosomes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [11] found that increased ROS production can trigger the NLRP3 inflammasome. Mitochondrial damage characterized by robust mitochondrial ROS generation and loss of membrane potential is linked to the NLRP3 inflammasome activation, and manipulations that block any of these processes inhibit inflammasome activation [22]. Our in vitro data demonstrates that ROS generation from high glucose exposure up-regulate the NLRP3 inflammasome activation and IL-1β protein and gene expression, and the ROS inhibitor NAC markedly down-regulates this effect.…”
Section: Discussionmentioning
confidence: 79%
“…While it has been demonstrated that ROS mediate induction of mitophagy, it is also important to consider whether impaired clearance of damaged mitochondria or poor quality control, the consequence in chronic ROS production, with its associated signaling [90, 91]. Mitochondrial ROS production is involved in ischemia/reperfusion injury [92].…”
Section: Consequence Of Disrupted Mitochondrial Quality Controlmentioning
confidence: 99%